Optical soliton solutions of dispersive Schrodinger-Hirota equation with chromatic and inter-modal dispersion in a couple of law medium - Onder, Ismail; Esen, Handenur; Secer, Aydin; Ozisik, Muslum; Bayram, Mustafa (SPRINGER, 2023)
In this paper, for the first time, we investigated the Kerr and parabolic law forms of the dispersive Schrodinger-Hirota equation in the presence of chromatic and inter-modal dispersions via the Sinh-Gordon equation expansion method. We gained dark, bright, kink and singular soliton solutions and we depicted their 3D, 2D, contour views. As an additional investigation, the effect of parameters on the model was examined and various 2D graphical simulations were portrayed.
Keywords: Schrodinger-Hirota equation; ShGEEM; Soliton solution; Chromatic dispersion; Inter-modal dispersion; Engineering; Physics; Optics